Chemical and sensory evaluation of a cream based soy milk (Glicine max) and ajonjolí milk (Sesamum indicum) (Agroindustria, Sociedad y Ambiente, 2019)
The growing interest of the food industry to offer alternatives to the global demand for food has contributed to the development of new food products that allow the use and preservation of raw materials used to prepare them and represent a new consumption option for population to which they are directed. The purpose of this research was to evaluate the chemical and sensory characteristics of a spreading cream based on a mixture of soy milk and sesame milk, to fulfill it an experimental design of two-component mixtures (proportion of soy milk and proportion of sesame milk) through which five protocols were established for the preparation of the mixture. Subsequently, the sensory assessment was carried out on a panel of 100 consumers, through an unstructured scale, to evaluate smell, taste, texture and spreadability. The spread cream that obtained greater acceptability was made with mixture A (90% soy milk - 10% sesame milk); The data of the texture and spreads attributes allowed developing models that showed the effect of soy milk and sesame milk concentrations on these attributes, but only the texture-related model allowed estimating that the best texture in the cream to spread obtained with 71.25% of soy milk and 28.75% of sesame milk, to achieve a response of 6.482 in texture. Finally, the chemical characteristics of the spread cream were evaluated, obtaining that, compared to another spreadable food such as mayonnaise, this new product has a nutritional balance with a higher protein content and a lower proportion of fat.
Keywords: Mixing design; emulsion; simplex-lattice